The Opposite Effects of Kynurenic Acid and Different Kynurenic Acid Analogs on Tumor Necrosis Factor-α (TNF-α) Production and Tumor Necrosis Factor-Stimulated Gene-6 (TSG-6) Expression - Mándi, Yvette; Endrész, Valéria; Mosolygó, Timea; Burián, Katalin; Lantos, Ildikó; Fülöp, Ferenc; Szatmári, István; Lőrinczi, Bálint; Balog, Attila; Vécsei, László (Frontiers in Immunology, 2019)
Purpose: The investigation of anti-inflammatory and immunosuppressive functions of Kynurenic acid (KYNA) is now in focus. There is also substantial evidence that TSG-6 has an anti-inflammatory activity. Therefore, in the present study, we compared the effects of newly synthetized KYNA analogues on the TNF-α production in U-937 monocytic cells in correlation with the effects on the TSG-6 expression. Methods: TNF-α production was measured by ELISA, the TSG-6 expression was determined by RTqPCR method. As cytokine inducers Staphylococcus aureus and Chlamydia pneumoniae were used. Results: KYNA and KYNA analogues attenuated TNF-α production and increased TSG-6 mRNA expression in U-937 cells stimulated by heat inactivated Staphylococcus aureus. In contrast, KYNA and some of the KYNA analoques increased the TNF-α production of C. pneumoniae infected U-937 cells; however, the newly synthetized analogues (SZR104, SZR 105 and SZR 109) exerted significant inhibitory effects on the TNF-α synthesis. The inhibitory and stimulatory effects correlated inversely with the TSG-6 expression. Conclusions: TSG-6 expression following activation with bacterial components could participate in the suppression of inflammatory cytokines, such as TNF-α, We suppose that the elevation of the TSG-6 expression by KYNA and especially by new KYNA analogues might be one of the mechanisms that are responsible for their suppressive effect on TNF-α production as a feedback mechanism. KYNA and KYNA analogues have an important role in influencing TSG-6 expression, and there is a possible benefit of targeting TSG-6 expression by kynurenines in inflammatory conditions following infections.